ENSEÑANZA DE LA FÍSICA DESDE LA PERSPECTIVA DEL APRENDIZAJE SIGNIFICATIVO EN ESTUDIANTES DE INGENIERÍAS - JUAN GUILLERMO NUÑEZ OSUNA (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2018)
Physics as a branch of factual science is closely related to the field of training of future engineers given the theoretical-practical processes that develop in the teaching-learning process and in our case we focus on meaningful learning giventhe advantages presented as a strategy because it leads us to different applications in context.Our general objective is toimplement a pedagogical proposal focused on meaningful learning to strengthen the learning of physics in the engineeringstudents of the Republican University Corporation.Our approach is mixed through the use of a field diary, a guide ofexperiments, a matrix of evaluation of activities as qualitative instruments which contain important indicators for the studyof the process and a matrix of evaluation of projects as a qualitative instrument where people external to the processevaluate the proposals of the students. From the pedagogical proposal implemented it is possible to enhance theunderstanding and application of the concepts and theories of the topics seen during the classes as a result of thetheoretical-practical component from the meaningful learning in coherence with the theoretical-practical nature ofphysics as a branch of the natural Sciences.